Continuity and change in family business genderstructures: an institutional perspective - Hytti, Ulla; Stenholm, Pekka; Alsos, Gry Agnete (Edward Elgar Publishing, 2025)
This chapter addresses gender structures of family business organizations. We take an institutional perspective to investigate how institutional arrangements influence gender structures in family firms and how they are sustained and altered. Our findings demonstrate that regulative, normative, and cognitive institutional elements influence changes or stability in gender structures of family firms over time. We identify change mechanisms, identified as institutional elements facilitating change in gender structures, and continuity mechanisms, interpreted as institutional elements hampering such change. The findings indicate that regulative, normative, and cognitive institutions interplay. Changes in gender structures demand that cognitive institutions are challenged from within family businesses. Furthermore, interaction between the family and business spheres influences the extent to which norms and cognitive institutions are challenged.
Women in Family Business: New Perspectives, Contexts and Roles